Exercise Improves Endothelial Function via the lncRNA MALAT1/miR-320a Axis in Obese Children and Adolescents - Wei Zhao; Yane Yin; Huiling Cao; Yandong Wang (Cardiology Research and Practice)
Background. Endothelial dysfunction commonly occurs in obese children and adolescents, leading to an increased risk of cardiovascular diseases. Exercise has significant protective effects against endothelial dysfunction through regulating some noncoding RNAs. This study aimed to investigate the relationship of long noncoding RNA MALAT1 and microRNA-320a (miR-320a) with the exercise-induced improvement of endothelial dysfunction in obese children and adolescents. Methods. Sixty obese children and adolescents were included in this study, including 40 cases that received 12-week exercise training and 20 cases that received only diet control. The anthropometric and blood indices before and after exercise were recorded and compared, and the endothelial dysfunction was evaluated by examining the levels of markers, including VCAM-1, ICAM-1, and E-selectin, using an ELISA assay. The expression levels of noncoding RNAs were assessed using real-time quantitative PCR, and their correlation with patients’ recorded indices and endothelial dysfunction markers was analyzed. Results. The 12-week exercise training significantly decreased the levels of VCAM-1, ICAM-1, and E-selectin and could inhibit MALAT1 but promote miR-320a expression in obese children and adolescents. The expression of MALAT1 and miR-320a was correlated with the changes in the anthropometric and blood indices of obese children and adolescents, and their correlations with endothelial dysfunction markers were obtained. Conclusion. All the data revealed that exercise has significantly protective effects against endothelial dysfunction and can regulate the expression of the MALAT1/miR-320a axis. MALAT1 and miR-320a were correlated with endothelial dysfunction markers, indicating that the MALAT1/miR-320a axis may be related with the alleviating effects of exercise on endothelial function in obese children and adolescents.